Islam and the European Union - Potz, Richard; Wieshaider, Wolfgang (Peeters, 2004)
In 2001, the European Consortium of Church and State Research focused its annual meeting on the highly topical issue of the legal position of Muslim communities in the European Union. The present book comprises updated analyses on Belgium, Germany, Greece, Spain, France, Italy, Austria and the United Kingdom. The studies extend from general questions of legal status to specific issues such as building mosques or cemeteries, ritual slaughter, and from language rights to family issues and education, thus providing an in-depth view of the legal framework for a developing European Islam.